Ecological and Evolutionary Consequences of Environmental Change and Management Actions for Migrating Fish - Tamario, Carl; Sunde, Johanna; Petersson, Erik; Tibblin, Petter; Forsman, Anders (Frontiers in Ecology and Evolution, 2019)
Migration strategies in fishes comprise a rich, ecologically important, and socioeconomically valuable example of biological diversity. The variation and flexibility in migration is evident between and within individuals, populations, and species, and thereby provides a useful model system that continues to inform how ecological and evolutionary processes mould biodiversity and how biological systems respond to environmental heterogeneity and change. Migrating fishes are targeted by commercial and recreational fishing and impact the functioning of aquatic ecosystems. Sadly, many species of migrating fish are under increasing threat by exploitation, pollution, habitat destruction, dispersal barriers, overfishing, and ongoing climate change that brings modified, novel, more variable and extreme conditions and selection regimes. All this calls for protection, sustainable utilization and adaptive management. However, the situation for migrating fishes is complicated further by actions aimed at mitigating the devastating effects of such threats. Changes in river connectivity associated with removal of dispersal barriers such as dams and construction of fishways, together with compensatory breeding and supplemental stocking can impact on gene flow and selection. How this in turn affects the dynamics, genetic structure, genetic diversity, evolutionary potential, and viability of spawning migrating fish populations remains largely unknown. In this narrative review we describe and discuss patterns, causes, and consequences of variation and flexibility in fish migration that are scientifically interesting and concern key issues within the framework of evolution and maintenance of biological diversity. We showcase how the evolutionary solutions to key questions that define migrating fish - whether or not to migrate, why to migrate, where to migrate, and when to migrate - may depend on individual characteristics and ecological conditions. We explore links between environmental change and migration strategies, and discuss whether and how threats associated with overexploitation, environmental makeovers, and management actions may differently influence vulnerability of individuals, populations and species depending on the variation and flexibility of their migration strategies. Our goal is to provide a broad overview of knowledge in this emerging area, spur future research and development of informed management, and ultimately promote sustainable utilization and protection of migrating fish and their ecosystems.